Supplementary Table S2 from Early On-treatment Changes in Circulating Tumor DNA Fraction and Response to Enzalutamide or Abiraterone in Metastatic Castration-Resistant Prostate Cancer - Sofie H. Tolmeijer (15313251) (2025)
Evidence for ctDNA estimates per patient per timepoint